The Help of HPV Integration Testing to Avoid the Misdiagnosis of a Patient with Stage Ia1 Cervical Cancer: A Case Report and Literature Review - Li J; Zhang X; Wang P; Li W (Dove Medical Press, 2021)
Jialu Li,1 Xiaoli Zhang,2 Pengpeng Wang,3 Weiping Li4 1Department of Obstetrics and Gynecology, The Second School of Clinical Medicine, Southern Medical University, Hainan Hospital of PLA General Hospital, Hainan, People's Republic of China; 2Department of Obstetrics and Gynecology, Three Medical Center, Chinese PLA General Hospital, Beijing, People's Republic of China; 3MyGenostics Inc., Beijing, People's Republic of China; 4Department of Obstetrics and Gynecology, Seven Medical Center, Chinese PLA General Hospital, Beijing, People's Republic of ChinaCorrespondence: Weiping LiDepartment of Obstetrics and Gynecology, Seven Medical Center, Chinese PLA General Hospital, Beijing, People's Republic of ChinaEmail liweiping258@sina.comAbstract: Screening and prevention in the early stage of cervical cancer could improve the 5-year survival rate of cervical cancer by up to 90%. The occurrence rate of human papillomavirus (HPV) integration has gradually increased with the development of cervical lesions. Here, we report the case of a 43-year-old woman diagnosed with chronic cervicitis based on cervical biopsy results. After medical consultation, surgery was recommended to the patient considering her 64 HPV integration sites and other biochemical and clinical test results. The pathology result of the conical biopsy obtained during operation confirmed that both her cervix and the glands had high-grade squamous intraepithelial lesion or cervical intraepithelial neoplasia III (HSIL/CIN III). The patient underwent uterectomy and bilateral salpingectomy and was discharged thereafter. The diagnosis of the patient was revised to stage Ia1 cervical cancer. The number of HPV integration sites is suggested to be an auxiliary indicator in the early screening of cervical cancer for predicting high-grade CIN and invasive cervical cancer.Keywords: HPV DNA, DNA methylation detection, cervical cancer, precancerous lesion of cervical cancer